Hermite-Hadamard Type Inequalities via the Montgomery Identity - Khan, Muhammad Adil; Khurshid, Yousaf; Chu, Yu-Ming (Communications in Mathematics and Applications, 2019)
The main aim of this manuscript is to prove the result for Hermite-Hadamard types inequalities and to strengthen our results by giving applications for means. The proof of the result is based on the Montgomery identity. We use the Montgomery identity to establish a new identity regarding the Hermite-Hadamard inequality. Based on this identity with a class of convex and monotone functions and Jensen's inequality, we obtain various results for the inequality. At the end, we also present applications for special bivariate means.